The Mechanism of Activation of Human Coagulation Factor X - Mertens, K.; Bertina, R.M. (Thrombosis and Haemostasis, 1979)
During the coagulation process factor X is converted to a serine protease, factor Xa. The present study concerns the molecular events which occur during the activation of human factor X by Russell’s viper venom and by the purified proteins of the extrinsic and intrinsic activator. Conversion of factor X was detected by amidolytic assays and SDS/polyacrylamide-gel electrophoresis.The results show that all activators convert factor X (MW 72,000) to an active form. In the presence of phospholipid the initially formed factor Xa (MW 54,000) complicates the further sequence of reactions by catalysing a) the conversion of factor Xa to a second active form (MW 50,000), b) the conversion of factor X to an inactive product (MW 59,000) by splitting off a peptide containing the active site serine, and c) the further degradation of the 50,000 and 59,000 components to a smaller component (MW 40,000).Comparison of these data with those reported for bovine factor X suggests that the mechanism of activation of human factor X is more complicated. The inactivation of both factor Xa and factor X by product factor Xa might be considered as important regulatory principles.